Peran ICJ dalam Upaya Penyelesian Sengketa Internasional Konflik Rusia dengan Ukraina (Perspektif Hukum Internasional) - Nugraha, M. Alief; Sabri, M.Ikhwan; Nuroni, Naela Siti; Khoiriyah, Qothrunnada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out what the ICJ actually does and its role in efforts to resolve the ongoing international dispute between Russia and Ukraine and to find out ways to resolve international law between Russia and Ukraine. The method used in this research is the normative legal method, namely research carried out by examining the laws and regulations that apply or are applied to a particular legal problem and then conclude with one's argument. The results of the discussion show that the ICJ has the authority to participate in resolving disputes between Russia and Ukraine. However, its authority is limited due to several reasons, including the choice to submit claims, politics and security, and characteristics of disputes.